Development of Green Composites Based on Castor Bean Shell (Ricinus communis) as Filler in Epoxy Resin Polymer - Ogah, Ogah Anselm; Joseph, Mbam Nwabueze; Pauline, Ojukwu Uju; Ohoke, Francis Okemini (Journal of Fibers and Polymer Composites, 2024)
The present study was carried out to develop composites using waste castor bean shell (CBS) as a filler and epoxy resin as a matrix. The composites were produced by varying the weight fractions of filler in the range of 5 to 35 wt%. The effects of castor bean shell filler weight percentages (0, 5, 10, 15, 20, 25, 30 and 35) on the tensile, flexural, impact and hardness properties of the epoxy/castor bean shell composites were evaluated using universal testing machine, hardness tester and scanning electron microscopy (SEM). The study revealed that the tensile strength, tensile modulus, flexural strength and impact strength increased with the increasing of the castor bean shell filler content. The highest tensile, flexural and impact properties of the CBS loaded epoxy composite were achieved at a filler content of 15wt%. The hardness increased with the increasing of the castor bean shell filler content. The water absorption and the thickness swelling increased with the increasing of the castor bean shell filler content. The swelling rates of the castor bean shell-epoxy polymer matrix composites are low during the initial stages of moisture absorption due to the visco-elasticity of the polymer matrix. The density decreased with the increasing of the castor bean shell filler content. SEM showed improved interfacial adhesion of the castor bean shell filler-epoxy resin matrix at 15wt% CBS content. The study has shown that castor bean shell filler is a viable reinforcement for manufacturing green composites from the viewpoint of their physical and mechanical properties.